Franjo Tudjman jako twórca chorwackiej niepodległości - Wawrzeńczak, Anna (Acta Universitatis Lodziensis. Folia Historica, 2007)
The author of this paper discusses role of Franjo Tudjman during the Yugoslav transformations and building of an independent of Croatia (between 1989 and 1992). The Croat’s growing preoccupation with the “national question” in ihe wake of the 1971-72 purge accompanied a steady growth of anti - Yugoslavia and pro - independence sentiment. It found delayed expression in Croatia’s first multiparty election in April-May 1990. ,The election won overwhemingly by the Croatian Democratic Union (HDZ). It’s leader, Franjo Tudjman, a historian and former general in the Yugoslav Army. He was Josip Broz Tito’s favourite untill there was conflict beetwen them. Tudjman started talking about Croatian’s bad situation and discrimination in Yugoslav. He was sacked in 1967 from the post of head of the party history institute in Zagreb. His attempts to correct what he saw as anti-Croat bias in official communist pronouncements concering World War two caused this. Tudjman was later twice arrested in 1972 and 1982 for “counter-revolutinary” nationalism, activity in “Croatian Spring” and for giving “hostile” interviews to the Western media about the situation in Croatia. Tudjman based his election campaign squarely on the “national question” and anti-Serbs and anti-semitism rhetoric. He paid little attention to the economy. He demanded sovereignty and independent of Croatia. He tackled the sucject of Ante Pavelic’s state without much apology to its victims. He said that NDH was “not only a quisling organization and Fascist crime, but was also an expresion of the Croatian nation’s historic desire for an independent homeland” . In Tudjman’s state, there were not place for Croatian Serbs. Tudjman said about discrimination of Croatians in Yugoslav’s administration, army and culture. The main reason of bad condition of Yugoslav and enemy of Croatia were Serbs. The war with Serbs from Slavonia and Krajina, who were helped by Belgrad and JNA was unavoidable. Tudjman was saying a lot about “democracy” and “building democratic Croatia” but his style of rule was more similar to communistic regime. For example, the new goverment was soon determined to control the media almost as much the old Communists. Instead of building independent and democratic Croatia, Tudjman aimed to strenghten nationalism, monoparty and strong dictatorship. After two years of rule Tudjman had a trouble. Croatia was in deep economic crisis Rising inflation and unemployment were the cause of an improverish society. At the and of war in early 1992, nearly one-third of Croatia’s territory remained under Serb control. It included the important east, which was some of the most fertile agricultural land. Before the second election in 1992 Tudjman regained the trust of Croatian people. However there was a lot of insoluble problems and then came something new. A new war came with the Serbs and a conflict in Bosnia and Hercegovina. Tudjman said at the time that Bosnia and Hercegovina should be given to Croatia. Just like Vojvodina was given to Serbia in 1945. The second election in 1992 Tudjman and his party won again. This time Tudjman openly aimed to war, threw any negotiations out. Again the main enemies were Serbs and Slobodan Milosevic. Tudjman built fear and terror in Croatia. He was too convinced of his great mission in Croatian history.